Exploring the genomic landscape of gummy stem blight resistance in watermelon through QTL-Seq - Purushothaman Natarajan; Akilan Rathnagiri; Luis A. Rivera-Burgos; Carlos Lopez-Ortiz; Yan Tomason; Padma Nimmakayala; Nebahat Sari; Todd C. Wehner; Amnon Levi; Umesh K. Reddy (BMC Plant Biology)
Abstract Background Watermelon is a nutritionally and economically significant crop in the US and globally. Gummy Stem Blight (GSB), caused by three cryptic Stagonosporopsis species, is one of the most devastating diseases affecting watermelon in the US, impacting most of the plant’s above-ground parts. This study aimed to identify key Quantitative Trait Variants (QTVs) that include SNPs and In/Dels associated with GSB resistance in selfed derivatives of advanced multicross interspecific derivatives population derived from intercrosses between the most resistant lines of Citrullus amarus and highly susceptible cultivars of Citrullus lanatus. Results Resistant and susceptible bulks were created by combining equimolar DNA concentrations from 30 extremely resistant derivatives and 30 extremely susceptible lines. These bulks underwent whole-genome sequencing, generating over 1 billion reads per bulk to achieve comprehensive genome coverage. The mapping percentage of the bulks to the parental genomes ranged from 92 to 99%. More than 6 million SNPs and 1 million indels were identified from the resistant parental genome, compared to fewer than 2 million SNPs and 0.4 million indels from the susceptible parental genome. QTNs associated with GSB resistance were identified using single-nucleotide polymorphism-index and Gprime methods. Statistically significant variants/loci linked to GSB resistance were found on chromosomes 1, 2, 3, 5, 7, 10, and 11. Notably, the genes Lipase class 3 family protein, Ribosome hibernation promotion factor (CaU02G00010), Ubiquitin-like-specific protease 1D (CaU03G04260), and Zinc finger CCCH domain-containing 15 (CaU03G10970) harbored the highest delta SNPs. Several previously published genes, including Avr9/Cf-9 Rapidly Elicited Protein (CaU07G12990) on chromosome 7, were also identified. Conclusions Identifying significant loci associated with GSB resistance has facilitated the development of PACE assays, which will aid in breeding GSB-resistant watermelon cultivars. These findings provide critical insights into the genetic basis of GSB resistance and represent a significant step towards improving the resilience of watermelon crops against this devastating disease.